Rechtliche Grundlagen der Wahl zum 20. Deutschen Bundestag am 26. September 2021 - Anna-Karina Elbert (WISTA - Wirtschaft und Statistik, 2021)
Der Beitrag beschreibt die rechtlichen Grundlagen der Wahl zum 20. Deutschen Bundestag und zeigt relevante Rechtsänderungen gegenüber der Bundestagswahl 2017 auf. Insbesondere erläutert er Änderungen des Bundeswahlgesetzes, der Bundeswahlordnung sowie die rechtlichen Maßnahmen, die aufgrund der COVID-19-Pandemie getroffen wurden, um die Wahl unter Pandemiebedingungen durchzuführen. – – This article describes the legal basis of the election to the 20th German Bundestag and presents relevant legal amendments compared with the Bundestag election of 2017. The focus is on amendments of the Federal Elections Act and the Federal Electoral Regulations as well as on legal measures taken on account of the COVID-19 pandemic to conduct the election under pandemic conditions.
Keywords: 519; Wahlrecht; Bundeswahlgesetz; Bundeswahlordnung; Sitzverteilung; Reformkommission; Wählbarkeit; right to vote; Federal Elections Act; Federal Electoral Regulations; distribution of seats; Reform Commission; eligibility to stand for election